2015
DOI: 10.3797/scipharm.1409-07
|View full text |Cite
|
Sign up to set email alerts
|

Improved Pharmacokinetics of Aceclofenac Immediate Release Tablets Incorporating ist Inclusion Complex with Hydroxypropyl-β-Cyclodextrin

Abstract: The present investigation reports the various pharmacokinetic parameters of immediate release aceclofenac tablets incorporating its inclusion complex with hydroxypropyl-β-cyclodextrin. The tablets were prepared using aceclofenac: hydroxypropyl-β-cyclodextrin in a 1:1 molar ratio by the direct compression method (TKN). The results were compared with those of the marketed brand (MKT) and pure drug (TAC). The P-values indicated that mean plasma concentrations were significantly different among all three formulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 3 publications
1
6
0
2
Order By: Relevance
“…Pharmacokinetic studies revealed that the optimized formulation (F2) of aceclofenac fast dissolving tablets reached peak plasma concentration in less time (1 sec) and with increased absorption and relative bioavailability (182.77) when compared to pure drug. These results were in agreement with the results obtained by Dahiya et al [21]. Summary of pharmacokinetic parameters was shown in table 8.…”
Section: Pharmacokinetics Studiessupporting
confidence: 93%
“…Pharmacokinetic studies revealed that the optimized formulation (F2) of aceclofenac fast dissolving tablets reached peak plasma concentration in less time (1 sec) and with increased absorption and relative bioavailability (182.77) when compared to pure drug. These results were in agreement with the results obtained by Dahiya et al [21]. Summary of pharmacokinetic parameters was shown in table 8.…”
Section: Pharmacokinetics Studiessupporting
confidence: 93%
“…Approximately 40% of existing small molecules and 70% of new candidates under development pipelines suffer from the low solubility problem, which is a major reason for their suboptimal drug delivery as well as failures in their development process. Approaches such as cyclodextrin complexation and solid dispersions have been employed to address this challenge and recommend the better formulation over their existing dosage forms [193][194][195][196][197][198]. Likewise, peptides, being biomacromolecules, also exhibit various challenges such as limited water solubility, stability aspects, as well as structural and synthesis complexities, limiting their full exploitation in drug development [199,200].…”
Section: Issues Associated With Marine Peptides In Drug Developmentmentioning
confidence: 99%
“…Henceforth, commonly recommended by the physicians of Asian and European countries [12]. Aceclofenac is a BCS (Biopharmaceutics Class System) class II drug with the log partition coefficient value of 2.170 [13]. The daily recommended dose of aceclofenac in an adult is 100 mg twice daily, necessitating adjustment of doses in hepatic impairments [10].…”
Section: Introductionmentioning
confidence: 99%